Indoor Millimeter-Wave Propagation Prediction by Measurement and Ray Tracing Simulation at 38 GHz - Hossain, Ferdous; Tan, Kim Geok; Rahman, Tharek Abd; Hindia, Mhd Nour; Dimyati, Kaharudin; Abdaziz, Azlan (MDPI, 2018)
The Millimeter-Wave (mmW) technology is going to mitigate the global higher bandwidth carriers. It will dominate the future network system by the attractive advantages of the higher frequency band. Higher frequency offers a wider bandwidth spectrum. Therefore, its utilizations are rapidly increasing in the wireless communication system. In this paper, an indoor mmW propagation prediction is presented at 38 GHz based on measurements and the proposed Three-Dimensional (3-D) Ray Tracing (RT) simulation. Moreover, an additional simulation performed using 3-D Shooting Bouncing Ray (SBR) method is presented. Simulation using existing SBR and the proposed RT methods have been performed separately on a specific layout where the measurement campaign is conducted. The RT methods simulations results have been verified by comparing with actual measurement data. There is a significant agreement between the simulation and measurement with respect to path loss and received signal strength indication. The analysis result shows that the proposed RT method output has better agreement with measurement output when compared to the SBR method. According to the result of the propagation prediction analysis, it can be stated that the proposed method's ray tracing is capable of predicting the mmW propagation based on a raw sketch of the real environment.